STUDI DESAIN DAN KOMPOSISI JENIS HASIL TANGKAPAN ALAT TANGKAP TRAP NET DI PERAIRAN KECAMATAN SIGERI KABUPATEN PANGKEP - Mustamin Tajuddin; Ihsan Ihsan; Asmidar Asmidar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
The research is entitled Utilization of coastal fisheries resources with trap net fishing equipment in the waters of Pangkep Regency. Related to that, the community uses the potential of fish resources in the coastal waters of Pangkep Regency with a variety of fishing gear, one of which is trap net (local read: tiku). Objectives are: 1) Knowing the composition of the type of trap net caught operated in coastal waters; 2) Knowing the level of environmental friendliness of the trap net fishing equipment operated in coastal waters 3) Knowing the economic feasibility of trap net fishing equipment operated in the coastal waters of Pangkep Regency. This research is expected to provide constructors regarding the composition of catches in the use of Coastal Fishing Ground resources with net trap fishing equipment in the waters of Pangkep Regency, South Sulawesi to ensure access to sustainable use of fisheries resources. The study was conducted in June - December 2018 in the coastal waters of Sigeri District, Pangkep Regency. Materials and tools related directly or indirectly to research to make measurements and observations in the field. The data needed consists of pruimer and secondary data. To achieve the goal, the data collected is carried out by analyzing fishing gear designs and analyzing the composition of catch species.The design of the trap net fishing gear is rectangular with a very small mesh size and the material is made of nylon (waring). The size of the trap net is 500 meters long and 1.5 meters wide. The composition of the types of trap net catches operated in the coastal waters of Pangkep Regency is very large and in general, fish that migrate daily at low tide take place.